Rivers for life : managing water for people and nature - Postel, Sandra. (Island Press, 2003)
Where have all the rivers gone? -- How much water does a river need? -- The policy toolbox -- Down to the river -- Building blocks for better river governance -- Epilogue : can we save Earth's rivers?